The Influence of Digital Marketing on Accounting Decisions: Implications and Challenges - Agus Triono Sudalyo, Ramadhian; Elfani Prasetyaningrum, Nurita (Ann Publisher, 2023)
Digital Marketing Digital marketing has become a key pillar of modern business strategy, changing the way companies interact with consumers and creating new opportunities. However, these developments also have significant ramifications in the realm of accounting decisions. This study aims to analyze the influence of digital marketing on accounting decision practices in the context of modern companies.This study uses qualitative and quantitative approaches to collect and analyze data. Data was obtained through a survey of marketing and accounting management from 15 companies in Boyolali Regency that adopted digital marketing strategies. The results of the study show that digital marketing has a significant impact on three main aspects of accounting decisions, namely revenue recognition, advertising spending, and valuation of digital assets. Revenue recognition becomes more complex due to variations in revenue recognition from e-commerce transactions, online promotions, and affiliate programs. Fluctuating advertising spending in a digital environment requires more adaptive methods of managing costs. Valuation of digital assets such as copyrights and websites faces challenges in assessing fair value which is more dynamic. The impact of digital marketing on accounting decisions creates challenges and opportunities as the business paradigm changes. This research provides important insights for companies in optimizing accounting decision making in the ever-evolving digital era.